PEMBERDAYAAN EKONOMI RAKYAT BERBASIS EKOWISATA MELALUI LEMBAGA PEMERINTAH DI GAYO LUES-ACEH - Sukri, Sukri (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Abstract: The Agusen Village area, Blangkejeren District, which is located in the hilly area of Gayo Lues Regency, has a long history. This village is a village where leprosy is dumped, the village is left behind and far from the city center, the level of education is low, economic growth is low, and this village is popularly known as the cannabis village. This study aims to reveal the efforts of government agencies in the Blangkejeren District in empowering the community's economy based on ecotourism and the stages of its empowerment to improve the economy of the Agusen Village community. The type of research used is field research with a descriptive approach. Data analysis by collecting data, reducing, presenting data and drawing conclusions. Based on the results of the study, it can be concluded that the collective ability of the community in promoting and developing tourism is implemented through systematic efforts made by local governments (sub-districts and districts); by providing non-formal education in increasing awareness, strengthening community capacity and strengthening village institutions as institutional bonds that foster harmonious harmony in building the Agusen community. Through various outreach activities, efforts were made to raise awareness of the potential existence of Agusen Village. Meanwhile, technical skills and skills in managing tourism-based economic activities are provided through the provision of training, both economically and technically.Keywords: Economic Empowerment; Ecotourism; Government Agencies.Abstrak: Kawasan Desa Agusen Kecamatan Blangkejeren yang berada di daerah perbukitan Kabupaten Gayo Lues memiliki sejarah yang cukup panjang. Desa ini merupakan desa tempat pembuangan penderita kusta, desa tertinggal dan jauh dari pusat kota, tingkat pendidikan rendah, pertumbuhan ekonomi rendah, dan desa ini populer dengan sebutan desa ganja. Penelitian ini bertujuan untuk mengungkap upaya lembaga pemerintahan Kecamatan Blangkejeren dalam pemberdayaan ekonomi masyarakat yang berbasis ekowisata dan tahapan pemberdayaannya untuk meningkatkan perekonomian masyarakat Desa Agusen. Jenis penelitian yang digunakan adalah penelitian lapangan dengan pendekatan deskriptif. Analisis data dengan mengumpulkan data, reduksi, penyajian data dan penarikan kesimpulan. Berdasarkan hasil penelitian dapat disimpulkan bahwa kemampuan kolektif masyarakat dalam memajukan serta mengembangkan pariwisata yang di implementasikan melalui upaya sistematis yang dilakukan oleh pemerintah daerah (kecamatan dan kabupaten); dengan memberikan pendidikan nonformal dalam meningkatkan kesadaran, penguatan kapasitas masyarakat dan memperkuat kelembagaan desa sebagai ikatan kelembagaan yang memupuk keharmonisan yang selaras dalam membangun masyarakat Agusen. Melalui berbagai kegiatan sosialisasi dilakukan upaya penyadaran akan potensi keberadaan Desa Agusen. Sedangkan keterampilan teknis dan keterampilan dalam mengelola kegiatan ekonomi berbasis pariwisata diberikan melalui pemberian pelatihan, baik secara ekonomi maupun teknis.Kata Kunci: Pemberdayaan Ekonomi; Ekowisata; Lembaga Pemerintah.